Prevalence Of Ectoparasites in Cattle in The Payakumbuh Livestock Market - Delli Lefiana (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
This study aims to determine the prevalence of ectoparasites infestation in cattle at the Payakumbuh Livestock Market. This research was conducted in August 2022. A total of 158 cows were randomly selected to be examined for ectoparasites at the Payakumbuh Livestock Market. Examination of ectoparasites using the permanent mounting method without staining. This study used a descriptive non-experimental design to obtain data on the incidence of ectoparasitic infestation in cattle at the Payakumbuh Livestock Market. Of the 158 cows examined, 85 of them were positive for ectoparasites on the outside of the body with a prevalence of 53.8%. Type of ectoparasites in the form of ticks Dermacentor sp. (50.63%) and Boophilus sp. (13.92%). Ectoparasites were found to be highest in cows with an infestation rate of 55.26% in the age group 8 years the prevalence reached 100% compared to the group of young cattle 56.36%.